2022
DOI: 10.1097/tp.0000000000003783
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Correlates, and Outcomes of Pulmonary Hypertension After Kidney Transplantation: Analysis of Linked US Registry and Medicare Billing Claims

Abstract: Background. The incidence, risks, and outcomes associated with pulmonary hypertension (P-HTN) in the kidney transplant (KTx) population are not well described. Methods. We linked US transplant registry data with Medicare claims (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) to investigate P-HTN diagnoses among Medicare-insured KTx recipients (N = 35 512) using billing claims. Cox regression was applied to identify independent correlates and outcomes of P-HTN (adjusted hazard ratio [aHR] 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…PH resolved in the cohort reported herein in 36 (59%) patients, a proportion similar to the number inferred from the data in the manuscript by Lentine et al 16…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…PH resolved in the cohort reported herein in 36 (59%) patients, a proportion similar to the number inferred from the data in the manuscript by Lentine et al 16…”
Section: Discussionsupporting
confidence: 90%
“…PH resolved in the cohort reported herein in 36 (59%) patients, a proportion similar to the number inferred from the data in the manuscript by Lentine et al 16 (50%). Herein it is reported that PH resolution occurred at a median of 37.5 months posttransplant.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations